(untitled) (Movimenta (ISSN 1984-4298), 2023)
Objective: to evaluate the physiotherapists perception about telerehabilitation of children with disabilities during the pandemic period. Materials and Methods: This is a descriptive and qualitative study, which utilized to data collection a Google Forms questionnaire and a semi-structured interview and to data interpretation a theme review. Results: It was interviewed eight physiotherapists that have as an occupation area neuropediatrics, having between five and 11 years of experience and have treated between five and 30 children via telerehabilitation, following these patients for 3 months to two years. Most of them mixed the sessions synchronous and asynchronous, using WhatsApp, approximately once a week for one hour and leaving orientations. It was identified, as facilitators, the increase of family participation in care and time flexibility and, as barriers, the lack of handling the children, the decrease of social interaction and the service difficult access. Conclusion: This type of follow-up was considered viable and beneficial by the professionals that participated in this research, amplifying the care and improving the access of children with disabilities to treatment and to orientations that facilitate/favor their development.